KRITIK DAN PANDANGAN ANALISIS TERHADAP TEORI RASIONALISASI TINDAKAN KOMUNIKATIF JÃRGEN HABERMAS - Dianpratiwi, Trikuntari (Jurnal Sejarah dan Budaya, 2009)
Abstract: The rationalization theory is one of some social theory that is important to face communication information age now. The expert that blowed this theory is Weber that suggested the conviction role and act in social change, but in contemporary social age now, Jürgen Habermas criticized this theory. The problems that make in communication and information age now is the present of cyber that lost face to face presenting. The context of communication setting of cyber world is much different to face to face world. Because of that, it is needed analysis to appropriate to rationalization theory, communication act rationalization theory especially. The irrationalization things that leads the subject past through rationalization follows in the footsteps irrationalization and reach act out of instinct. The new theory that was borned form the criticize to the communicative act of rationalization theory of Jürgen Habermas is the contextually communicative from irrationalization act rationalization theory (cyber world), where the context of communicative act cyber give much different influence to the fact. This theory is an alternatif of new theory of communicative act at post reality age now.